2008
DOI: 10.1093/nar/gkn148
|View full text |Cite
|
Sign up to set email alerts
|

An ultraconserved Hox–Pbx responsive element resides in the coding sequence of Hoxa2 and is active in rhombomere 4

Abstract: The Hoxa2 gene has a fundamental role in vertebrate craniofacial and hindbrain patterning. Segmental control of Hoxa2 expression is crucial to its function and several studies have highlighted transcriptional regulatory elements governing its activity in distinct rhombomeres. Here, we identify a putative Hox–Pbx responsive cis-regulatory sequence, which resides in the coding sequence of Hoxa2 and is an important component of Hoxa2 regulation in rhombomere (r) 4. By using cell transfection and chromatin immunop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 73 publications
1
67
0
1
Order By: Relevance
“…Given that several eExons were previously discovered to regulate the gene they reside in (Neznanov et al 1997;Lampe et al 2008;Tumpel et al 2008;Ritter et al 2012), we explicitly set out to search for coding eExons that do not autoregulate but rather could regulate their nearby genes. This was of interest to us due to the phenotypic consequences that coding mutations could have on their nearby genes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that several eExons were previously discovered to regulate the gene they reside in (Neznanov et al 1997;Lampe et al 2008;Tumpel et al 2008;Ritter et al 2012), we explicitly set out to search for coding eExons that do not autoregulate but rather could regulate their nearby genes. This was of interest to us due to the phenotypic consequences that coding mutations could have on their nearby genes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a recent study scanning for synonymous constraint in protein coding regions (Lin et al 2011) found an overlap between two of these eExons (Lampe et al 2008;Tumpel et al 2008) and synonymous constraint elements. Here, we analyzed 25 available ChIP-seq data sets of enhancer marks (H3K4me1, H3K27ac, and EP300, also known as p300) for their overlap with coding exons.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…They share the ability to bind and regulate certain target genes and enhancers in the hindbrain (Alexander et al, 2009;Lampe et al, 2008;Matis et al, 2007), but they display opposite activities in regulating oligodendrocyte precursor cells in this territory. Indeed, Hoxa2 has been shown to inhibit whereas Hoxb2 promotes oligodendrogenesis at its early steps.…”
Section: Intra-pg Comparisons: From Functional Equivalence To Neo-or mentioning
confidence: 99%
“…Gateway® expression vectors for AD-Hoxa2, DB-Hoxa2 and FLAG-Hoxa2 [26], construction of expression vectors for Hoxa2 [31], pCMVlacZ [32], pCMV-PBX1a [33], pCS2-Prep1 [34], Hoxa2 r4 HRE enhancer [35] and the pKS-Hoxa2 [36] plasmids have been described elsewhere. Gateway® entry vectors (pEnt) for human KPC2 (refers as UBAC1) was obtained from the hORFeome v3.1 (http://horfdb.dfci.harvard.edu) [37] and HOXA1, HOXA2, HOXA3, HOXC4, HOXB5, HOXD10 and HOXC11 genes were obtained from the hORFeome v7.1 (http://horfdb.dfci.harvard.edu/hv7/).…”
Section: Plasmid Constructsmentioning
confidence: 99%